Replacing soybean meal with Narbon vetch (Vicia narbonensis L.) in pig diets: composition of subcutaneous fat and fresh loin, and sensory attributes of dry-cured product - Wendy M. Rauw; Luis Gomez-Raya; Mercedes Martín-Pedrosa; Miguel A. Sanz-Calvo; Eduardo de Mercado-de la Peña; Juan J. Ciruelos; Emilio Gómez-Izquierdo (Spanish Journal of Agricultural Research, 2021)
Aim of the study: To evaluate the consequences for pork quality traits of replacing soybean meal with Narbon vetch in pig diets. Area of study: Castilla-Leon, Spain. Material and methods: 48 Duroc × Iberian barrows were fed diets with 0% (V0), 5% (V5), 10% (V10) and 20% (V20) inclusion of Narbon vetch. Pork quality traits investigated were 1) intramuscular fat, protein and moisture content of fresh loin, 2) fatty acid composition of subcutaneous fat, and 3) sensory attributes (Triangle test and a Simple Difference Test with a non-trained taste panel) of cured loin. Main results: Inclusion of Narbon vetch in the diet showed no significant effect on intramuscular fat, protein and moisture in fresh loin samples. Stearic acid was higher in subcutaneous fat of V5 than in V0 and V10 (p < 0.05), and oleic acid was higher in V10 than in V0, V5 and V20 (p < 0.05); no other differences in fatty acid composition were observed. Taste panelists tended to be able to distinguish V10 from V0 cured loins (p < 0.10), and were able to distinguish V20 from V0 loins (p < 0.05), in particular due to a perceived difference in taste, texture and marbling. No differences in intensity of the texture, marbling, aroma and color of cured loins were found between V0 and V5. Research highlights: Inclusion of Narbon vetch in pig diets did not significantly affect fresh loin composition or fatty acid composition of subcutaneous fat. Consumers perceived a difference in sensory characteristics of cured loin with replacement of soybean meal with Narbon Vetch, but they did not characterize this as more favorable.